2022
DOI: 10.1200/po.21.00444
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives and Experiences of Parents and Adolescents Who Participate in a Pediatric Precision Oncology Program: "When You Feel Helpless, This Kind of Thing Is Very Helpful"

Abstract: PURPOSE The SickKids Cancer Sequencing (KiCS) Program, launched in 2016, evaluates the clinical utility of paired tumor/germline Next-Generation Sequencing (NGS) in pediatric oncology patients with hard-to-cure and rare cancers. In anticipation of further widespread adoption of NGS, we aimed to characterize the experiences and perspectives of adolescents and parents of patients who have already undergone NGS evaluation, focusing on the psychosocial impact and personal utility. METHODS Parents of patients with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 27 publications
0
22
0
Order By: Relevance
“…It is possible that younger adolescents may have received simpler verbal explanations of the trial’s complexity or moderated their intake of diagnosis‐ and treatment‐related information 11 . The current study did not explore patients’ actual understanding of precision medicine; however, a recent Canadian study found that adolescents had more realistic expectations of receiving actionable results from precision medicine testing than their parents 48 …”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…It is possible that younger adolescents may have received simpler verbal explanations of the trial’s complexity or moderated their intake of diagnosis‐ and treatment‐related information 11 . The current study did not explore patients’ actual understanding of precision medicine; however, a recent Canadian study found that adolescents had more realistic expectations of receiving actionable results from precision medicine testing than their parents 48 …”
Section: Discussionmentioning
confidence: 84%
“…11 The current study did not explore patients' actual understanding of precision medicine; however, a recent Canadian study found that adolescents had more realistic expectations of receiving actionable results from precision medicine testing than their parents. 48…”
Section: Discussionmentioning
confidence: 99%
“…25,26,28 In general -regardless of the outcome of the genetic testingclinically increased psychological distress after genetic testing in children was rare. 23,24,26,28,29,31,33,[36][37][38][39][40] Most studies focused on anxiety, depression and/or worry. When these emotions were reported, adolescents 2 generally described them as 'mild'.…”
Section: Negative Emotionsmentioning
confidence: 99%
“…In the event of a favorable result, receiving good news was experienced as a form of closure as they learnt that they were not more at risk than other children. 37,39 Interestingly, children also mentioned feeling relieved as a consequence of witnessing relief in their parents. 33 In the event of an unfavorable result, some children reported feeling relieved of uncertainty and hopeful about having better health outcomes than older generations in their family, now that they were aware of their predisposition.…”
Section: Positive Emotionsmentioning
confidence: 99%
“…Emerging data suggest that difficulties accessing therapeutic agents are challenging for both parents [ 27 ] and clinicians [ 29 , 32 ] and can contribute to the decision not to implement a targeted therapy [ 33 ]. Alongside these challenges is the possibility that engaging in the precision medicine process, even if ultimately unsuccessful, may benefit patient QoL by giving a patient and their family hope and reassurance that they have explored all potential treatment possibilities [ 29 , 34 , 35 ]. Identifying aspects of the precision medicine process which impact patient QoL will inform tailored psychosocial support for patients and families.…”
Section: Introductionmentioning
confidence: 99%